Rapid and facile preparation of nanocomposite film heaters for composite manufacturing - Naseri, Iman; Ashrafi, Behnam; Jakubinek, Michael; Martinez-Rubi, Yadienka; Yourdkhani, Mostafa (Frontiers in Materials, 2023)
Nanocomposite film heaters are promising for out-of-oven (OoO) and energy-efficient curing of fiber-reinforced polymer composites. However, the current techniques for manufacturing nanocomposite film heaters are intensive in terms of time and energy and require expensive resources. In this work, we present a facile and rapid approach for preparation of nanocomposite film heaters with excellent heat generation properties based on a frontally polymerizable resin system. This approach enables rapid fabrication of nanocomposite films within a few minutes and without the need for using expensive equipment, making it suitable for mass production of nanocomposite film heaters. Various characterization techniques are used to determine the morphology, composition, and mechanical properties of nanocomposite films. The electrothermal performance of nanocomposite film heaters are then evaluated under various conditions. Nanostructured heaters exhibit excellent Joule heating properties, where temperatures as high as ~132 °C can be reached within only 2 min using a low input power density of ~2 W cm-2. Finally, a nanocomposite film heater is used for OoO curing of a small composite panel with minimal energy consumption. Using this approach, 0.1 MJ of energy is consumed during the four-hour cure cycle of a commercial prepreg system, which would otherwise require at least 40.5 MJ of energy to cure using a convection oven.